ANALYSIS OF FACTORS INFLUENCING PATIENT SATISFACTION TAKE CARE OF TO LODGE AT SELASIH HOSPITAL IN AREA SUB-PROVINCE OF PELALAWAN - Rafles Rafles (Jurnal Ekonomi, 2014)
This Research aim to to know how storey;level satisfaction of patient take care of to lodge pursuant to quality of service given by Hospital of Area Sub-Province of Pelalawan which consist of reliability, assurance, emphaty, tangibles, and responsiveness. Sampel which is used in this research amount to 100 responder. As for method intake of sampel by using sampling purposive. Research instrument stem from kuesioner which in processing with program of SPSS 16.0 Windows for.Result of research indicate that quantitatively the quality of service as a whole have influence which is signifikan to satisfaction of patient. dimension of tangibles, reliability, assurance and emphaty get assessment with good category, whereas variable of emphaty variable and of responsibility get assessment with good enough category. dimension of tangibles represent dimension is quality of dominant service have an effect on to satisfaction of patient. dimension of emphaty have an effect on signifikan to satisfaction of patient, while dimension of reliability, assurance, and responsiveness not have influence of signifikan to satisfaction of patient.